Ethnobotanical study in a village at Rukum District, Nepal - Bhatta, L.R. (Banko Janakari, 2017)
The present study gives information on the indigenous use of various plants locally available at Vijayashori Village Development Committee (VDC) of Rukum District. Forty-four species have been reported to be used for various purposes that include medicine, food, furniture making, agricultural implements, etc.